Tunable power-dependent upconversion emission of co-doped Er$^{3+}$--Tm$^{3+}$ nanoparticles for bioimaging - Tran Thu Huong,; Ha Thi Phuong,; Le Thi Vinh,; Hoang Thi Khuyen,; Pham Thi Lien,; Do Thi Phuong,; Nguyen Thi Nga,; Do Thi Thao, (Communications in Physics, 2026)
Lanthanide-doped upconversion nanoparticles (UCNPs) have emerged as promising platforms for bioimaging and theranostics owing to their unique ability to convert near-infrared (NIR) excitation into visible emission. Controlling their emission behavior is critical for both mechanistic understanding and biomedical translation. In this work, we synthesized NaYF4: Yb3+, Er3+, Tm3+ UCNPs via a hydrothermal route and systematically investigated their power-dependent luminescence. Log--log slope analysis clarified photon participation in different emission bands, revealed competition between Yb3+ → Er3+ and Yb3+ → Tm3+ pathways, and identified saturation effects at higher excitation power. Based on these insights, the nanoparticles were functionalized with silica--TPGS to improve colloidal stability, dispersibility, and biocompatibility. Preliminary biological evaluation with MCF-7 breast cancer cells demonstrated efficient uptake, bright intracellular luminescence, and dose-dependent cytotoxicity (GI50 = 0.26 ± 0.02 ppm). These findings highlight excitation-power control as a powerful strategy for tailoring UCNP emission properties, laying the foundation for advanced applications in ratiometric sensing, multicolor imaging, and cancer theranostics.